Consumption of argan oil (Morocco) with its unique profile of fatty acids, tocopherols, squalene, sterols and phenolic compounds should confer valuable cancer chemopreventive effects - Khallouki, Farid; Younos, C.; Soulimani, R.; Oster, T.; Charrouf, Z.; Spiegelhalder, Bertold; Bartsch, Helmut; Owen, Robert (European journal of cancer prevention, 2003)
The aim of this study was to evaluate the fatty acids, tocopherols, squalene, sterols and phenolic antioxidants in three types of argan oil (Moroccan food, Moroccan aesthetic and a French commercial variety) along with a basic comparison with extra virgin olive and sunflower oil. The fatty acid profiles in the argan oils were very similar, with oleic acid (43%) and linoleic acid (36%) and their respective monoacylglycerols predominating. The major vitamer identified was γ-tocopherol with a mean of 483±11 mg/kg, in contrast to α-tocopherol, which is the major vitamer in olive (190±1 mg/kg) and sunflower oil (532±6 mg/kg). The squalene content of the argan oils was very similar with a mean of 313±4 mg/100 g, which is lower than that of the olive oil (499 mg/100 g) but significantly higher than in the sunflower oil (6 mg/100 g). In contrast to olive and sunflower oils in which β-sitosterol is predominant, the major sterols detected in the argan oils were schottenol (mean 147±10 mg/kg) and spinasterol (mean 122±10 mg/kg). The only phenolic compounds other than the tocopherol vitamers which could be readily detected and quantitated were vanillic, syringic and ferulic (probably conjugated to glucose) acids along with tyrosol. In contrast to the extra virgin olive oil (793 mg/kg), the concentration of total phenolic compounds is extremely low (<5.0 mg/kg). Nevertheless, argan oil with its high content of the vitamer γ-tocopherol, squalene and oleic acid is likely to enhance the cancer prevention effects of the Moroccan diet.